(untitled) (REMUNOM, 2026)
This study provides an integrated analysis of the recent literature on agricultural commodities and investments by combining bibliometric analysis and systematic review methods. The research aims to map the scientific evolution of the field, identify the main themes, methodological approaches, and existing research gaps, with particular emphasis on the absence of studies focusing on Investment Funds in Agribusiness Production Chains (FIAGROs). The data were collected from the Web of Science database, covering articles published between 2021 and 2025. After successive filtering procedures by subject area, document type, language, and period, 56 studies were selected for the systematic review. The bibliometric analysis, conducted using the Biblioshiny software, reveals a consistent growth in scientific output until 2024, a concentration of publications in finance and applied economics journals, and a strong contribution from countries such as China, India, and the United States. Based on a detailed examination of the selected articles, the systematic review identified four main thematic clusters: Price, Risk, Hedge, and Investment. The findings indicate a predominance of studies focused on price dynamics, volatility, market connectedness, and the effects of financialization, with extensive use of advanced econometric models, including GARCH and its extensions, TVP-VAR, quantile models, panel data models, and time-frequency approaches.Despite the methodological robustness and the maturation of the international literature, a significant gap remains: the absence of empirical studies examining agricultural funds as investment vehicles, particularly in the Brazilian context. In this regard, the study highlights the originality and relevance of future research investigating the relationship between agricultural commodity price fluctuations and the performance of FIAGROs. By integrating bibliometric and systematic evidence, this study advances the academic debate and provides conceptual and methodological foundations for further research in agribusiness finance.